Exercise Duration Affects Session Ratings of Perceived Exertion as a Function of Exercise Intensity. Issue 4 (August 2021) - Jesus, Raille Silva de; Batista, Rebecca Évelyn Santos; Santos, Vinícius Moura Eça; Ohara, David; Alves, Eduardo da Silva; Ribeiro, Luiz Fernando Paulino
Session ratings of perceived exertion (sRPE) are considered a practical marker of whole session exercise intensity, but its relationship to exercise volume has remained unclear. We analyzed the effects of exercise duration at different intensities on overall and differentiated sRPE. Sixteen males ( Mage  = 22.6, SD  = 2.2 years; M height  = 176.4, SD  = 5.8 cm; M weight  = 74.0, SD  = 5.9 kg; and M body fat  = 9.4, SD  = 2.2%) performed 15 and 30 minute runs at speeds associated with RPE levels of two (weak), three (moderate) and five (strong) on Borg's CR-10 scale during a previous graded exercise test. We used Foster's scale to access sRPE 30 minutes after each trial. Significant increases in sRPE were found with increases in running speed (p  < 0.01, η G 2  = 0.48) and duration (p  < 0.01, η G 2  = 0.16), with a significant speed X duration interaction (p  < 0.01, η G 2  = 0.10). In addition, there was a significant effect for sRPE type (p  = 0.01, η G 2  = 0.05) in that overall sRPE was slightly lower than sRPE differentiated to legs and higher than sRPE differentiated to breathing through the trials. Changes in sRPE from 15 to 30-minute trials were minimal for the slow speed and weak sRPE (Cohen´s dz = 0.04 – 0.25) but got higher at the moderate (Cohen´s dz = 0.88 – 1.06) and strong (Cohen´s dz = 1.94 – 2.50) speeds and sRPEs. Thus, exercise duration affects sRPE in an intensity dependent manner. This finding has practical relevance for prescribing exercise, suggesting a need to target specific training loads or aims to optimize trainees' retrospective perceptions of the exercise experience.